Early outcomes of laparoscopic donor nephrectomy with multiple renal arteries - Fernando Meyer; Sandro A. Nichele; Ari Adamy; Luiz Sergio Santos; Christiano Machado (International Brazilian Journal of Urology, 2012)
PURPOSE: We evaluated our experience with laparoscopic donor nephrectomy in patients with multiple renal arteries, comparing operative outcomes and early graft function with patients with a single renal artery. MATERIALS AND METHODS: From January 2003 to February 2009, 130 patients underwent laparoscopic donor nephrectomy at our institution, 108 (83%) with a single renal artery and 22 (17%) with multiple arteries. Donor and recipient outcomes for single artery and multiple arteries allografts were compared. RESULTS: The LDN operative time was similar between the single artery and multiple arteries groups (162 vs 163 min, respectively, p = 0.87). Allografts with multiple arteries had significantly longer warm ischemia time (3.9 vs 4.9 min, p = 0.05) and cold ischemia time (72 vs 94 min, p < 0.001) than those with single artery. The conversion rate was similar between single and multiple arteries groups (6% vs 4.5%, respectively, p = 0.7). Multiple arteries grafts had a non statistically significant higher rate of poor graft function when compared to single artery grafts (23% vs 12%, respectively, p = 0.18). Five patients in the single artery group (4.6%) and one patient in the multiple arteries group (4.5%) needed dialysis during the first postoperative week. Overall, recipient complication rates were similar between single and multiple arteries groups (12.9% vs 18.1%, respectively, p = 0.51). CONCLUSION: Laparoscopic donor nephrectomy with multiple arteries was associated with a non statistically significant higher rate of poor early graft function. The procedure appears to be safe in patients with multiple arteries, with similar complications rates. Multiple arteries should not be a contraindication for laparoscopic donor nephrectomy.